2020
DOI: 10.1177/2041731420965797
|View full text |Cite
|
Sign up to set email alerts
|

The combination of multi-functional ingredients-loaded hydrogels and three-dimensional printed porous titanium alloys for infective bone defect treatment

Abstract: Biomaterial with the dual-functions of bone regeneration and antibacterial is a novel therapy for infective bone defects. Three-dimensional (3D)-printed porous titanium (pTi) benefits bone ingrowth, but its microporous structure conducive to bacteria reproduction. Herein, a multifunctional hydrogel was prepared from dynamic supramolecular assembly of sodium tetraborate (Na2B4O7), polyvinyl alcohol (PVA), silver nanoparticles (AgNPs) and tetraethyl orthosilicate (TEOS), and composited with pTi as an implant sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(31 citation statements)
references
References 64 publications
(68 reference statements)
0
31
0
Order By: Relevance
“…Many experiments have been performed in various fields, such as tissue engineering, to determine the antibacterial effects of nonantibiotic materials [7][8][9]. One of the nonantibiotic materials with antibacterial activity is a natural product.…”
Section: Introductionmentioning
confidence: 99%
“…Many experiments have been performed in various fields, such as tissue engineering, to determine the antibacterial effects of nonantibiotic materials [7][8][9]. One of the nonantibiotic materials with antibacterial activity is a natural product.…”
Section: Introductionmentioning
confidence: 99%
“…As a representation, 3D printing manufacturing technology is applied to prepare porous biocompatible scaffolds with excellent mechanical and bone conduction properties (Bittner et al, 2019;Diloksumpan et al, 2020;Polley et al, 2020). Qiao et al (2020) demonstrated a multifunctional hydrogel scaffold from supramolecular assembly of sodium tetraborate (Na 2 B 4 O 7 ), polyvinyl alcohol (PVA), Ag NPs, and tetraethyl orthosilicate (TEOS). These 3D composite scaffolds with suitable pore size and matched bone porosity exhibited good antibacterial and biological activity, which promoted BMSC proliferation and osteogenic differentiation and inhibited bacteria.…”
Section: Advances In Tissue-engineered Bone Technologymentioning
confidence: 99%
“…Qiao et al ( 72 ) proposed a three-dimensional printed porous titanium alloy (Ti 6 Al 4 V) embedded in an antibacterial hydrogel to prevent infections. The porous structure made the implant more compatible with host bone tissue, as it avoided stress-shielding and osteolysis.…”
Section: Role Of Metallic Biomaterials In Orthopedics and Dentistrymentioning
confidence: 99%